The Role of Algorithms in Improving the Accuracy of Intelligent Employee Selection in Human Resource Management at PT. Rasaki Logam Makmur Bandung - Granit Agustina; Rudi Suprianto Ahmadi; Herni Suryani Apandi; Feby Febrian; Ahmad Zaelani Adnan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2026)
This study aims to examine the efforts of algorithms to improve the accuracy of intelligent employee selection in Human Resource Management (HRM) at PT. Rasaki Logam Makmur Bandung. Using qualitative research methods, this study identified that algorithms can improve employee selection accuracy by analyzing broader data and discovering ways unknown to humans. High employee quality can improve employee and organizational performance. Good productivity satisfaction can increase work quality and reduce errors. Good employee performance can increase productivity satisfaction and reduce stress. Good selection accuracy can improve employee and organizational performance by selecting the most suitable employees for available positions. Intelligent employee selection can improve the quality of selected employees and reduce selection errors. The results show that the use of algorithms can improve employee quality, job satisfaction, and employee performance. This study also developed an algorithm-based intelligent employee selection model that can improve the effectiveness and efficiency of employee selection methods. The algorithm can be used as an intelligent employee selection engine by analyzing candidate data and predicting their suitability for available positions. This study adds impetus to the development of HRM theory and practice, and provides recommendations for companies to improve employee quality through the use of algorithms in the employee selection process. It can serve as a reference for companies and HRM practitioners to improve employee quality through the use of algorithms in the employee selection process. Therefore, companies need to pay attention to these factors in the employee selection process to improve employee quality and performance. By using an intelligent, algorithm-based employee selection model, companies can increase the effectiveness and efficiency of their employee selection process and select the most suitable candidates for available positions.